Improving congruence: setting the stage for meaningful interactions with experts - Zvi Shik, Jonathan (Improving University Science Teaching and Learning, 2023)
Congruence between didactic elements in a course can foster deep learning in higher education (Mørcke & Rump, 2015). These didactic elements include aspects of learning support, student backgrounds and goals, and the framework of course management (Hounsell et al., 2005). The concept of constructive alignment is further woven into the fabric of congruence and includes didactic elements of teaching and learning activities (TLAs), aims stated in the curriculum, and approaches for assessment and feedback (Hounsell et al., 2005). One of the main duties of a teacher is to keep these ships pointed in the same direction, and to continuously communicate to students throughout the course about how each element is progressing or being sustained.